Comparing autonomous and class-based learners in Brazil: Evidence for the present-day advantages of informal, out-of-class learning. (October 2016) - Cole, Jason; Vanderplank, Robert
Abstract: In the last ten years, there has been a steady increase in reported cases of successful high-level acquisition by out-of-classroom, informal learners through the affordances of the Internet, while mainstream SLA research has continued to focus on instructed learning contexts with assessments often relying on classroom-based tasks. In this article, we report a study comparing high-level, well-motivated Central Brazilian classroom-trained learners (CTLs) with fully autonomous self-instructed learners (FASILs). Thirty-four FASILs and fifty CTLs, matched for socio-economic status, age, educational level and years of English learning, were assessed on seven distinct but related aspects of language proficiency, completed a questionnaire and were interviewed to gather data on behaviour, beliefs and attitudes. FASILs scored significantly higher than CTLs on all assessments while questionnaires and interviews revealed key differences in attitudes and motivational development. Mode of learning correlated significantly with grammatical and lexical knowledge and range, with detailed analysis indicating that fossilized errors in high-frequency structures were significantly more common among CTLs than FASILs. The results reveal how the new affordances for naturalistic learning through the Internet have transformed informal language learning, enabling significant numbers of independent, informal learners in foreign language contexts to achieve very high levels of proficiency.